Mobility and working opportunities in the EU and Slovakia - Bajzikova, L'ubica (Array, 2020)
Current globalisation processes witness the mobility and migration of labour as their characteristic features. The free movement of people and workers is one of the rights of citizens of the European Union (EU), and includes the right to move, to reside and to work in an EU member state without discrimination. The aim of this paper is to analyse the labour mobility within the EU with special attention to Slovakia. In its historical development, Slovakia belonged to countries with population migrating predominantly to foreign countries and was not a traditional destination country for migrants. However, today it has gradually become a state that employs foreign labour, especially in production plants. This change has not only been contributed to by Slovakia’s accession to the EU, but especially by the economic development of the state and the creation of new job opportunities for both domestic and foreign labour. The study analyses the intra-mobility in Slovakia and focuses on analysis of the trends in employment of foreign workers from EU and non-EU member states between 2007 and 2019. For the purposes of this paper, data were extracted from a relatively large number of prominent sources, for example: the European Commission, Eurostat, and the International Labour Organization (ILO) reports, and the Slovak Statistical Office resources related to labour mobility. In the desk research, the collected information were analysed and subjected to critical multidimensional assessment from quantitative, absolute, and relative, as well as cross-sectional perspectives. Special attention was paid to analysis of documentation that accompanied these data. The significance of the examined topic is underlined by the fact that Slovakia is currently a recipient of foreign labour due to insufficient qualification of domestic labour.